IP-10 acts early in CV-A16 infection to induce BBB destruction and promote virus entry into the CNS by increasing TNF-α expression - Hu, Yajie; Hu, Yunguang; Yin, Anguo; Lv, Yaming; Li, Jiang; Fan, Jingyuan; Qian, Baojiang; Song, Jie; Zhang, Yunhui (Frontiers in Immunology, 2024)
The mechanisms underlying pathological changes in the central nervous system (CNS) following Coxsackievirus A16 (CV-A16) infection have not yet been elucidated. IFN-γ-inducible protein-10 (IP-10) is often used as a predictive factor to monitor early virus infection. It has also been reported that IP-10 plays a pivotal role in neuroinflammation. In this study, we aimed to explore the role of IP-10 in the neuropathogenesis of CV-A16 infection. We observed that the level of IP-10, as well as the TLR3-TRIF-TRAF3-TBK1-NF-κB and RIG-I/MDA5-MAVS-TRAFS-TBK1-NF-κB pathways, which are the upstream of IP-10, were significantly elevated during the course of CV-A16 infection. This increase was accompanied by an increase in a series of inflammatory cytokines at different time-points during CV-A16 infection. To determine whether IP-10 influences BBB integrity, we examined junctional complexes. Our results revealed that the expression levels of Claudin5, Occludin, ZO-1 and VE-Cadherin were notably decreased in CV-A16-infected HUVECs, but these indicators were restored in CV-A16-infected HUVECs with Eldelumab treatment. Nevertheless, IP-10 is only a chemokine that primarily traffics CXCR3-positive immune cells to inflammatory sites or promotes the production of inflammatory cytokines. Therefore, the interactions between IP-10 and inflammatory cytokines were evaluated. Our data revealed that IP-10 mediated the production of TNF-α, which was also observed to change the junctional complexes. Moreover, in a suckling mouse model, IP-10 and TNF-α treatments exacerbated clinical symptoms, mortality and pathological changes in the brain of CV-A16-infected mice, but Anti-IP-10 and Anti-TNF-α treatments alleviated these changes. Our data also revealed that IP-10 may be detected early in CV-A16 infection, whereas TNF-α was detected late in CV-A16 infection, and the production of TNF-α was also found to be positively correlated with IP-10. In addition, IP-10 and TNF-α were observed to reduce junctional complexes and enhance virus entry into the CNS. Taken together, this study provides the first evidence that CV-A16 activates the IP-10/TNF-α regulatory axis to cause BBB damage and accelerate the formation of neuroinflammation in infected hosts, which not only provides a new understanding of the neuropathogenesis caused by CV-A16, but also offers a promising target for the development of CV-A16 antiviral drugs.